Assasins: Between History and Legend - Shirinov, Agil (Scholarya Demo Journal of Ruby, 2021)
After the death of the Fatimid Caliph Al-Mustansir Billah (1036-1094), the Ismaili branch of Shia Islam was divided into two parts. Al-Mustanṣir Billah's youngest son Aḥmad al-Mustaʿlī Billah, with the help of his brotherin-law, the vizier Afdal ibn Badr al-Jamali, became a Caliph. During the reign of the new Caliph, the proponents of Mustansir’s older son Nizar’s imamate were subjected to prosecution. Nizariyya, which, unlike Musta’liyya accepted the Imamate of Nizar, became an official ideology of the Ismaili State, (which was) founded in Alamut by Hasan al-Sabbah. Hasan al-Sabbah was attempting to spread Nizari Ismailism in the Muslim East and, by using various ideological and military means including assassination, was struggling against those who posed obstacles in his way. This activity, which began with the capture of Alamut, later on, expanded towards Syria by the efforts of Rasid al-Din Sinan (1126-1193), and thus Nizaris became a military and ideological force in the Islamic World. Nizaris, who, due to their use of narcotics called Hashish were named by their opponents as Hashishis (Assassins), on one hand by propagandizing their ideology based on the necessity to obey their imams, and on the other hand by using the tactics of assassination against their enemies, which had been unprecedented until that time, became a fearful movement. One of the main targets of the Seljuks was the military and ideological struggle with them. At last, Assassins ceased to be a serious force in the Muslim world after Mongols seized Alamut and killed the Nizari Imam and, later on, the Mamluks took control of Syrian Nizaris. There is a significant amount of information on the Assassins’ activities in the historical sources and travels written by medieval Muslim and European authors. Although some of those works reflected historical facts as they are, others, Marco Polo being in the first place, based their information on legends. The main purpose of the article is, by being based on the real sources, to determine the right and legendary pieces of information on the Assassins and thus to reveal the historical facts on this issue.